DEVELOPMENT OF EMPLOYABILITY SKILLS ASSESSMENT TOOL FOR MANUFACTURING INDUSTRY (Jurnal Mekanikal, 2018)
Mastering employability skills is one of the global problems which employers are facing with graduates or their future employees. Various research on employability skills have been conducted nationally and internationally and it was found that many technical graduates nowadays are lack of employability skills rather than technical skills. The main goal of this research is to develop an employability skill assessment tool using the Kepner-Tregoe (K-T) method in which weight factor is set. Samples for this research consisted of 107 employers from five types of Malaysian manufacturing industry. The results showed that employers in all five categories of manufacturing industry are in consensus on the importance for all seven of the employability skills. These skills were ranked as follows; interpersonal skills, thinking skills, personal qualities/values, resource skills, system and technology skills, basic skills and informational skills. From these means, an employability skills assessment tool was developed using the K-T Method and an Employability Skills Assessment Tool Development Model was produced
Keywords: Employability skill; employability skill assessment tool; weight factor.